Sudden cardiac death in ischaemic heart disease: coronary thrombosis or myocardial fibrosis?. (21st April 2023) - Prati, Francesco; Gurguglione, Giovanni; Biccire, Flavio; Cipolloni, Luigi; Ferrari, Michela; Di Toro, Alessandro; Arbustini, Eloisa
Abstract: The mechanisms underlying sudden cardiac death (SCD) in patients with ischaemic heart disease (IHD) caused by coronary atherosclerosis are not yet clarified. For decades, acute coronary causes have been sought as the main triggers of SCD in these patients. In fact, angiographic and pathological studies in cardiac arrest survivors and SCD victims, respectively, consistently show that acute plaque events occur in ∼50% of SCD of patients with IHD. Among the acute events, plaque rupture and erosion triggering acute coronary thrombosis remain the main substrates; however, a significant percentage of plaque haemorrhage (20%) is identified by pathological studies. Its role in acute coronary thrombosis is unknown and deserves future intravascular imaging developments. In the remaining 50% of SCD, the atherosclerotic coronary disease shows the characteristics of structural stability. More recent studies have focused attention not only on the coronary tree and on the search for acute complications of atherosclerotic plaques but also on myocardial tissue, identifying replacement and patchy fibrosis as the most frequent findings in the post-mortem hearts of these patients, a feature followed by cardiac hypertrophy, as assessed by the heart weight, usually associated with fibrosis. The possibility of characterizing myocardial fibrosis in vivo, besides confirming the pathological data, now offers new risk stratification perspectives to prevent SCD in IHD, alongside the consolidated secondary prevention criteria based on left ventricular dysfunction.